Superconductivity in a Hubbard-Frohlich model and in cuprates - Thomas M. Hardy; J.P. Hague; John Samson; A.S. Alexandrov (2009)
Using the variational Monte Carlo method, we find that a relatively weak long-range electron-phonon interaction induces a d-wave superconducting state in doped Mott-Hubbard insulators and/or strongly correlated metals with a condensation energy significantly larger than can be obtained with Coulomb repulsion only. Moreover, the superconductivity is shown to exist for infinite on-site Coulomb repulsion without the need for additional mechanisms such as spin fluctuations to mediate d-wave superconductivity. We argue that our superconducting state is robust with respect to a more intricate choice of the trial-wave function and that a possible origin of high-temperature superconductivity lies in a proper combination of strong electron-electron correlations with poorly screened Fröhlich electron-phonon interaction.